Greenhouse gas balance from cultivation and direct land use change of recently established sugarcane (Saccharum officinarum) plantation in south-central Brazil - De Oliveira Bordonal, Ricardo [UNESP]; Lal, Rattan; Alves Aguiar, Daniel; De Figueiredo, Eduardo Barretto [UNESP]; Ito Perillo, Luciano [UNESP]; Adami, Marcos; Theodor Rudorff, Bernardo Friedrich; La Scala, Newton [UNESP] (Elsevier, 2015)
Inventorying greenhouse gas (GHG) balance associated to sugarcane (Saccharum officinarum) based ethanol is critical to assess the degree of carbon (C) neutrality of biofuels. Few studies have considered the GHG emissions from sugarcane cultivation while taking direct land use change (dLUC) into account. This study was conducted to enhance scientific understanding of the GHG balance related to sugarcane cultivation while considering dynamics of all C pools (biomass and soil) upon conversion of diverse land uses into sugarcane during 2006-2011 in south-central Brazil. Based on a comprehensive evaluation of survey data and given that the sugarcane cultivation and dLUC can be credibly assessed by using remote sensing satellite images, estimations of GHG emissions were performed using the IPCC methodologies and expressed in terms of Tg CO2eq (Teragram=1012 g=1 million Mg) considering a 20-year time horizon. The overall accumulated GHG balance was 217.1 Tg CO2eq by 2030, with an emission of 481.6 Tg CO2eq from sugarcane cultivation being offset by a biomass C sink of -274.5 Tg CO2eq. Soils had an almost neutral C budget with a slight emission of 10.0 Tg CO2eq by 2030. Nevertheless, the ethanol C offset by displacing fossil fuels could readily payback that C deficit and ensures the environmental benefits of sugarcane ethanol. Our results show an increase of C reservoirs (biomass and soil) through conversion of arable and pastoral lands into sugarcane, and a decrease of C reservoirs when citrus, plantation forest and natural forest are converted to sugarcane. Here we support that the impact of dLUC on biomass and soil C pools must be considered while expanding sugarcane plantation as an important mechanism for GHG abatement beyond the avoided emissions through use of sugarcane ethanol.
Keywords: Bioenergy; C offset; Climate change; Ethanol production; Inventory; Sugarcane harvest; Sustainability